Unraveling Java’s Prowess and Adaptable Architecture in Modern Software Development - Baddam, Parikshith Reddy; Vadiyala, Vishal Reddy; Thaduri, Upendar Rao (Global Disclosure of Economics and Business, 2018)
This research delves into the multifaceted landscape of the Java programming language, elucidating its fundamental strengths and adaptive architecture that have dominated the software development realm for nearly two decades. The study meticulously explores the objectives of deciphering Java’s platform independence, leveraging its object-oriented paradigm, and evaluating its expansive ecosystem. By examining the findings related to Java’s role in cross-platform development, web and mobile application development, enterprise software, and the Internet of Things (IoT), this research sheds light on the language’s unparalleled versatility. The author’s contribution lies in synthesizing a comprehensive overview of Java’s features, from its robust security measures to its extensive standard library. This research underscores Java’s pivotal role in shaping the ever-evolving landscape of software development and concludes with implications for future advancements in the field.